Internalisasi Nilai Religius pada Novel Bidadari Berbisik Karya Asma Nadia di Sekolah Menengah Atas - Dewi Ratnaningsih; Alfina Susanti; Sri Widayati (Edukasi Lingua Sastra, 2023)
Internalization is an effort to instill values ​​and norms into a person. The internalization of religious values ​​in the novel Whispering Angel by Asma Nadia in high school is an interesting study to do. The purpose of this study is to describe the internalization of religious values ​​contained in Asma Nadia's novel Whispering Bidadari and describe the learning plan for internalizing religious values ​​contained in Asma Nadia's Whispering Bidadari novel in high school. The method used in this research is descriptive method with a qualitative approach. The results of the study show that there is a religious value in the Whispering Angel novel, namely 1) the relationship between humans and God, 2) the relationship between humans and oneself, 3) the relationship between humans and other humans, and 4) the relationship between humans and nature. Based on the results of the study, religious values ​​in the novel Whispering Angel by Asma Nadia can be internalized to high school students. Teachers can internalize the religious values ​​contained in the novel into students by designing learning competencies and objectives, learning materials or materials, methods, strategies, and learning evaluations. Then, the teacher carries out the learning steps which consist of opening, learning core, and closing.